TrustE - An Emotional Trust Model for Agents - Bitencourt, Guilherme K.; Silveira, Ricardo A.; Marchi, Jerusa (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Trust and Reputation has been proposed in the Multiagent System area as a way for assisting agents to select good partners in order to increese the well successed interactions between agents. As well as trust, agent emotions has been studied with the intention to turn actions and reactions of the agents more human like. In this paper, we present a trust emotional based model. This proposal is an hibrid model that congregates a mathematical and a symbolical models for capturing the complexity of the reasoning. Quantitative and qualitative evalutations are mixed throught the incorporation of some emotional flavors in the trust evaluation.